Kesehatan dan Lingkungan dalam Perspektif Sejarah: Perkembangan Baru Historiografi Indonesia - Emalia, Imas (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
This article will explain the new developments in Indonesian history writing since entering the 2000s. The theme of health and the environment is increasingly in demand among academics, including historians. The 2019 coronavirus disease (covid) phenomenon that has hit most parts of the world brings various lessons to human life, including learning history. Among academics, researchers, historians, and students, writing on the theme of health and the environment continues to stretch as if it is a new trend. This period can be said to be the period of 'performance' of health and environmental research. Both of these themes have become prima donna in various campus events, health institutions, and places of worship. Until now, the two themes are still in demand by history students. Unfortunately, the guidelines or framework of reference (Learning Program Units/SAP) do not yet exist, so it seems there is